PELATIHAN EVALUASI PEMBELAJARAN JARAK JAUH DAN PEMBUATAN WEBSITE BERBASIS KURIKULUM MERDEKA DI SDN 5 KARANGSARI - Siska Aprilia Hardiyanti; Eka Afrida Ermawati; Aprilia Divi Yustita; Tri Maryono Rusadi; Yuni Ulfiyati (LPPM Universitas Bina Bangsa, 2022)
During the covid-19 pandemic, learning was carried out in accordance with the principles contained in the Minister of Education and Culture Decree No. 4 of 2020. The Minister of Education and Culture has also made various innovations in developing the educational curriculum, namely the Independent Learning Curriculum. The existence and role of information technology in the education system has brought about a new era of development in the world of education, but these developments have not been matched by an increase in human resources. This service program is in the form of distance learning evaluation training and the creation of an independent curriculum-based website at SDN 5 Karangsari. The event began with the provision of material on the independent learning program followed by workshops and learning evaluation training that supports independent learning such as Quizizz and Kahoot. The solutions offered for partners are the Service Team developing the making of practical IT-based learning evaluations so that they can improve the quality of teachers and create a pleasant learning atmosphere in accordance with the independent learning program, foster student interest in technology, and provide teaching to teachers in making Cognitive questions based on Higher Order Thinking Skill (HOTS). In addition, the Service Team also teaches the management of school websites for the benefit of providing information to the public about SDN 5 Karangsari